Digital Marketing Strategy to Enhance the Competitiveness of Muslim Fashion SMEs: : A Case Study of Yabunaya Muslim Store - Rahayu, Cindy; Christanti, Yunitasari; widjaja, Nathanael (SEEIJ (Social Economics and Ecology International Journal), 2024)
Tenun Ikat Troso, an indigenous weaving craft originating from Jepara, specifically Troso village, involves the intricate process of weaving fabric from warp and weft threads that are initially tied and dyed using natural pigments. The weaving apparatus employed for this task is the automated power loom (ATBM) (Ismanto, Tamrin, & Pebruary, 2018). The enterprising Mrs. Rahayu, who owns UMKM Yabunaya Muslim Store, embarked on her business journey in 2017. She ventured into both selling and personally manufacturing modest dresses, utilizing an assortment of Indonesian textiles, including batik prints, stamped batik (batik cap), hand-drawn batik (batik tulis), a fusion of stamped and hand-drawn batik, and handwoven fabrics created using traditional weaving tools. Mrs. Rahayu, equipped with skills acquired through private fashion courses under the guidance of industry experts at the Susan Budiharjo School (Cikini), financed her endeavors independently without any business partners. Notably, her designs remain authentically original, with no replication of other designer products. UMKM Yabunaya Muslim Store has diversified its fabric sourcing, encompassing batik fabrics from Solo, Riau, Madura, Pekalongan, Kebumen, woven fabrics from Troso, Jepara, and sasirangan fabrics from Kalimantan. The store has successfully produced approximately 60 sets of batik, Troso woven fabrics, and sasirangan dresses. Mrs. Rahayu has actively participated in exhibitions and bazaars, maintaining a strong online presence through Google My Business, while also effectively marketing her products on platforms like Instagram, Facebook, and various other social media channels.